Are Patients Acknowledged in Clinical Research? A Systematic Survey (Principles and Practice of Clinical Research, 2022)
Background: Study participants make meaningful contributions to clinical research. It is unknown if these contributions are recognized in scientific literature. Our primary aim was to assess the trends of recognition of the study participants' contributions in the acknowledgments section of clinical research articles.Methods: We conducted a systematic survey to assess the trends in study participants and staff members— understanding staff as those who contribute to the development of the project— in acknowledgments in the scientific literature from 1990 to 2019. We included peer-reviewed original research from the top ten general and internal medicine journals with the highest impact factor.Results: 496 studies were included in the analysis. 110 (22.2%) articles acknowledged study participants and 291 (58.7%) acknowledged staff. In the last five years there has been an increase in the recognition of study participants in both observational and experimental studies by 28.3% and 112.6%, when compared to fifteen years ago (2005-2009). The frequency of staff acknowledgment stratified by study design has remained constant.Conclusion: Most of the clinical articles fail to acknowledge study participants’ contributions to research. We encourage authors to recognize their participation when appropriate and journals to provide guidance on how to acknowledge participants and staff members.